Rancang Bangun Aplikasi Penentuan Pemenang Lomba Pada Badan Perpustakaan dan Kearsipan Provinsi Jawa Timur Berbasis Web - Aldian, Rosik Fivin; ., Sulistiowati; ., Romeo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
The criteria number of decision maker sometimes become a problem. We can solve that problem using set of alternatives based on the criteria. Problems like this are often known by the term Multiple Attribute Decision Making (MADM). In this research will be appointed a case that is Determination of Winners of Library Competition At Badan Perpustakaan & Kearsipan Province East Java. The search for weighted values is done through an objective approach. This study is done by finding the value for each criterion, then done ranking to determine the optimal alternative.